Intent and Extreme Negligence As Elements of Criminal Offenses Against the Environment - Milošević, Mladen; Banović, Jovana (Glasnik Advokatske komore Vojvodine, 2026)
Continuous attention is devoted to a healthy environment in almost all spheres of human activity: from civic activism and various development strategies to legal regulation and the sanctioning of violations of the right to clean water, air, soil, flora and fauna. Criminal law protection represents an important segment of these efforts, ranging from “classic” environmental harms and endangerment, such as pollution, to those offences that elevate environmental crime to a “higher level” and turn it into a profitable activity. One of the factors contributing to this situation is the inefficiency of criminal justice mechanisms, as well as the limited effectiveness of penalties where they have been applied. This was one of the motives behind the adoption of Directive 2024/1203 on the protection of the environment through criminal law. In addition, some of the key questions of criminal law doctrine can be observed almost paradigmatically through environmental criminal offences. This primarily refers to certain substantive dilemmas concerning the subjective elements of these offences; the concept of corporate criminal liability, whose potential may be most fully realised precisely in the field of environmental crime; and the boundaries and justification of criminal law intervention, particularly in relation to administrative, civil and other punitive measures. The Directive and relevant international sources predominantly operate with the notions of intent and gross (or serious) negligence as the subjective components of criminal offences. This reflects a dominant characteristic of the Anglo-Saxon legal tradition, whose structure of the general concept of a criminal offence differs in several respects from the Continental model. Still, the subjective element stands as a distinct component – whether through the mens rea framework or through the concept of culpability. Broadly speaking, intent(ion) and serious (gross) negligence – the subjective forms envisaged by the Directive – may be considered counterparts to domestic concepts of intention and negligence. However, the assumption is that these notions overlap only in certain aspects and that it would be unwarranted to equate them without careful consideration. Nevertheless, the Directive contains a provision instructing that these elements be interpreted in accordance with national law, which, with certain specificities, relativises this hypothesis. Accordingly, the focus of the paper will be on analysing these subjective elements within the framework of environmental criminal offences and the meaning of the terms prescribed by Directive 2024/1203. Furthermore, we will examine the possibilities of implementing these provisions into domestic law and highlight the capacities of the existing Criminal Code in this area. Finally, an attempt will be made to formulate practical guidelines for understanding and applying the norms on intent and gross (serious) negligence, with a view to facilitating their more effective proof in practice.
Keywords: environmental criminal offences; intent; intention; gross negligence; serious negligence; Directive 2024/1203; environment